2008
DOI: 10.1242/dev.024133
|View full text |Cite
|
Sign up to set email alerts
|

Rho inhibition recruits DCC to the neuronal plasma membrane and enhances axon chemoattraction to netrin 1

Abstract: Molecular cues, such as netrin 1, guide axons by influencing growth cone motility. Rho GTPases are a family of intracellular proteins that regulate the cytoskeleton, substrate adhesion and vesicle trafficking. Activation of the RhoA subfamily of Rho GTPases is essential for chemorepellent axon guidance; however, their role during axonal chemoattraction is unclear. Here, we show that netrin 1, through its receptor DCC, inhibits RhoA in embryonic spinal commissural neurons. To determine whether netrin 1-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
83
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 80 publications
9
83
1
Order By: Relevance
“…It has been shown that Netrin-1 triggers membrane exposure of DCC-containing vesicles in growth cones (Bouchard et al, 2004;Moore et al, 2008). First, we corroborated that incubation with Netrin-1, but not with control media or BDNF (which acts via TrkB receptors), caused the mobilization of DCC from the inside of growth cones to the cell membrane ( Fig.…”
Section: Netrin-1 Regulates the Association Of DCC And Sytx1supporting
confidence: 80%
See 1 more Smart Citation
“…It has been shown that Netrin-1 triggers membrane exposure of DCC-containing vesicles in growth cones (Bouchard et al, 2004;Moore et al, 2008). First, we corroborated that incubation with Netrin-1, but not with control media or BDNF (which acts via TrkB receptors), caused the mobilization of DCC from the inside of growth cones to the cell membrane ( Fig.…”
Section: Netrin-1 Regulates the Association Of DCC And Sytx1supporting
confidence: 80%
“…For instance, chemoattractant guidance cues may lead to increased exocytosis, thereby resulting in membrane extension in a given direction of growth. Recent studies have shown that PKA (protein kinase A) activation recruits DCC to the plasma membrane and enhances axon chemoattraction to Netrin-1 (Bouchard et al, 2004;Moore et al, 2008). Indeed, recent studies showed that local increases of Ca 2Ï© result in asymmetric exocytosis in the growth cone (Tojima et al, 2007) and that clathrin-mediated endocytosis is essential for Semaphorin 3A-induced chemorepulsion (Tojima et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…4A and 4B); consistent with earlier work using cortical neurons. [36][37][52][53] The presence of receptors in all subcellular regions is in agreement with the notion that neurons may be sensing differences in Netrin-1 concentration along their entire lengths to modulate their elongation rates, and across their growth cones to modulate turning responses. Signal intensities were measured at three axonal regions of interest (ROIs): axon shafts, growth cones and filopodia (Fig.…”
supporting
confidence: 82%
“…Netrin-1 stimulation recruits multiple signal transduction molecules, such as Fyn, FAK, PAK1, P130 CAS , TRIO, and DOCK180, through DCC to form a signaling complex (41, 43, 68 -70), which then activates small GTPases Rac1 and Cdc42 (44,46,63,64,(71)(72)(73) or inhibits RhoA in Netrin-induced attraction (74). Toxin B, an inhibitor of the small GTPases Rho, Rac, and Cdc42, not only blocked Netrin-1-induced Rac1 activity but inhibited the induction of phospho-JNK1 by Netrin-1 without affecting phospho-p38 (Fig.…”
Section: Discussionmentioning
confidence: 99%